Bacilli in the breast - Thyagarajan, Mohanapriya; Nallasivam, Mahin; Singh, Balaji (International Surgery Journal, 2017)
Background: Breast tuberculosis is uncommon even in countries where the incidence of pulmonary and extra pulmonary tuberculosis is high. The incidence of breast tuberculosis is less than 1% of the total breast pathologies in the world. Methods: This is a prospective study wherein all cases of breast tuberculosis with age above 18 years with only primary breast tuberculosis in both sexes. A total of 40 patients were diagnosed with breast tuberculosis. Most of the patients were treated as outpatient. All the patients were subjected to Imaging (Ultrasonagram or Mammogram) and fine needle aspiration cytology (FNAC). When FNAC was in conclusive, core needle biopsy was done. When none of the investigations were contributive, patient was subjected to excision biopsy. The tissue was sent for histopatho logical examination, gene xpert, AFB culture and sensitivity. Results: Diagnosis of breast tuberculosis was confirmed in all the 40 patients either with fine needle aspiration cytology or biopsy. All patients were with anti-tuberculous treatment as per the Revised National Tuberculosis Control Program of India (RNTCP). All patients responded well and had complete recovery. Overall prognosis of breast tuberculosis was good. Conclusions: Breast tuberculosis is often mistaken for carcinoma breast. Clinical examination often fails to differentiate carcinoma breast from tuberculosis and a high index of suspicion is necessary. Mammography is not of much help as the findings in carcinoma in advanced stage are similar to that of tubercular lesion.